Kuchnia tradycyjna jako czynnik wpływający na rozwój turystyki regionu na przykładzie Krajny = Traditional Kitchen as a factor in the development of tourism in the region as an example Krajna - Banaczkowska, Alicja; Eksterowicz, Jerzy; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Banaczkowska Alicja, Eksterowicz Jerzy, Zukow Walery. Kuchnia tradycyjna jako czynnik wpływający na rozwój turystyki regionu na przykładzie Krajny = Traditional Kitchen as a factor in the development of tourism in the region as an example Krajna. Journal of Education, Health and Sport. 2016;6(2):47-63. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45767 http://ojs.ukw.edu.pl/index.php/johs/article/view/3377 https://pbn.nauka.gov.pl/works/713068 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Kuchnia tradycyjna jako czynnik wpływający na rozwój turystyki regionu na przykładzie Krajny Traditional Kitchen as a factor in the development of tourism in the region as an example Krajna Alicja Banaczkowska1, Jerzy Eksterowicz2, Walery Zukow2 1Wyższa Szkoła Gospodarki, Bydgoszcz 2Uniwersytet Kazimierza Wielkiego, Bydgoszcz Słowa kluczowe: kuchnia tradycyjna, turystyka, Krajna. Keywords: traditional kitchen, tourism, Krajna. Streszczenie Wstęp Niniejsze opracowanie dotyczy wpływu walorów lokalnej kuchni tradycyjnej na rozwój turystyki. W tym ujęciu wskazany został region kulturowy Krajny, tzw. ziemi pogranicza. Podjęto się omówienia powyższego zagadnienia ze względu na potrzebę i jednocześnie obowiązek czerpania z dziedzictwa kulturowego, z pożytkiem dla rozwoju społeczeństwa. Przykładem takiego działania dającego impuls dla rozwoju turystyki może być wykorzystanie smaków i aromatów dawnej kuchni polskiej, jako atrakcji przyciągającej turystów. Cel pracy Celem przeprowadzanych badań jest określenie wpływu kulturowo-etnicznych walorów regionu (kuchnia regionalna) na rozwijanie się funkcji turystycznej w danym regionie na przykładzie Krajny. Obszar wybrany został z uwagi na zainteresowanie tematyką propagowania elementów kultury ludowej oraz możliwości realizacji tematu w tym posiadane kompetencje, czas i środki techniczne. Nie bez znaczenia są też własne doświadczenia współautorki, która początkowo była odbiorcą przekazu sztuki ludowej, a następnie także jej animatorem. Problemy i hipotezy badawcze Problem badawczy według ( Frakfort'a-Nachmias'a, 2001) to bodziec intelektualny wywołujący reakcję w postaci badań naukowych. Problem badawczy może być ustanowiony jako zdanie twierdzące lub pytające, a samo sformułowanie problemu polega na określeniu pytania, na które albo jeszcze nie ma odpowiedzi, albo nie jest ona dostatecznie precyzyjna. Jest formułowany za pomocą określonych pojęć, które odzwierciedlają zjawiska empiryczne. Hipoteza badawcza jest to wstępna odpowiedz na postawiony problem, dająca się sprawdzić empirycznie (należy ją zweryfikować w toku badań). W niniejszej pracy wyodrębniono następujące problemy badawcze oraz hipotezy: Problem główny: Jaki jest stopień oddziaływania tradycyjnej kuchni na wzrost zainteresowania danym regionem zarówno przez potencjalnych turystów jak i lokalnych mieszkańców? Problemy szczegółowe: Jaki jest poziom zainteresowania kuchnią regionalną wśród mieszkańców województw: głównie wielkopolskiego, pomorskiego i kujawsko-pomorskiego (ze względu na przynależność administracyjną Krajny)? Jaka jest wiedza na temat potraw staropolskich i regionalnych? Czy w świadomości społecznej funkcjonuje pojęcie restauracji typu karczma oferującej regionalne jedzenie? Czy Krajna jako region kulturowy jest rozpoznawalna? Czy kuchnia regionalna jest atrakcyjna? Czy atrakcyjność kuchni regionalnej może być czynnikiem decydującym o wyborze miejsca wypoczynku lub podróży? Czy metody promocji produktów regionalnych są wystarczające? Hipoteza główna: Zakłada się, że stopień oddziaływania tradycyjnej kuchni na wzrost zainteresowania danym regionem zarówno przez potencjalnych turystów jak i lokalnych mieszkańców jest wysoki. Hipotezy szczegółowe: Zakłada się, że poziom zainteresowania kuchnią regionalną wśród mieszkańców województw: wielkopolskiego, pomorskiego i kujawsko-pomorskiego (ze względu na przynależność administracyjną Krajny) jest na średnim poziomie. Zakłada się, że wiedza na temat potraw staropolskich i regionalnych jest na średnim poziomie. Zakłada się, że w świadomości społecznej, w stopniu umiarkowanym funkcjonuje pojęcie restauracji typu karczma oferującej regionalne jedzenie. Zakłada się, że Krajna jako region kulturowy jest rozpoznawalna. Zakłada się, że kuchnia regionalna jest atrakcyjna. Zakłada się, że atrakcyjność kuchni regionalnej może być czynnikiem decydującym o wyborze miejsca wypoczynku lub podróży w stopniu wysokim. Zakłada się, że metody promocji produktów regionalnych są niewystarczające. Metody, techniki i narzędzia pomiaru Zastosowane metody badawcze w niniejszym opracowaniu to: sondaż diagnostyczny, a jako główną technikę przyjęto badania ankietowe, kwestionariusz ankiety składający się z 6 pytań, w większości zamkniętych, został wypełniony online przez próbę 117 respondentów. Badania miały zmierzyć poziom wiedzy o potrawach regionalnych oraz zainteresowania Krajną jako regionem kulturowym. Z uwagi na wysoką ocenę atrakcyjności potraw tradycyjnych kuchni regionalnej, postanowiono potwierdzić dany punkt badań ankietowych przy pomocy technik wspierających proces badawczy, jakimi są obserwacja oraz wywiad swobodny-terenowy. Obserwacje i wywiad swobodny- terenowy , który stanowiły poniekąd badanie opinii konsumentów, przeprowadzono na próbie 52 osób, zadbano o to aby próba ta reprezentowała osoby w różnym wieku zamieszkujące na wsi i w mieście. Wyniki Badań i ich omówienie Charakterystyka badanej grupy/próby Badania sondażowe zostały przeprowadzone na próbie 117 osób z doboru losowego prostego, w przedziale wiekowym 19-30 lat. Ludzie ci są mieszkańcami województw: wielkopolskiego, pomorskiego, kujawsko-pomorskiego. Badani respondenci pochodzili zarówno z obszarów wiejskich jak i miejskich. Weryfikacja hipotez Weryfikacja przeprowadzona w oparciu o łączne wyniki badań wykazała, że potwierdziło się siedem z ośmiu założonych hipotez. Hipoteza nr 1 zakładająca, że stopień oddziaływania tradycyjnej kuchni na wzrost zainteresowania danym regionem zarówno przez potencjalnych turystów jak i lokalnych mieszkańców jest wysoki, w pełni potwierdziła się. Hipoteza nr 2 zakładająca, że poziom zainteresowania kuchnią regionalną wśród mieszkańców województw: wielkopolskiego, pomorskiego i kujawsko-pomorskiego jest na średnim poziomie, nie potwierdziła się Hipoteza nr 3 zakładająca, że wiedza na temat potraw staropolskich i regionalnych jest na średnim poziomie, potwierdziła się. Hipoteza nr 4 zakładająca, że w świadomości społecznej, w stopniu umiarkowanym funkcjonuje pojęcie restauracji typu karczma oferującej regionalne jedzenie, potwierdziła się. Hipoteza nr 5 zakładająca, że Krajna jako region kulturowy jest rozpoznawalna, potwierdziła się. Hipoteza nr 6 zakładająca, że kuchnia regionalna jest atrakcyjna, potwierdziła się. Respondenci ocenili kuchnię regionalną jako szczególnie atrakcyjną. Hipoteza nr 7 zakładająca, że atrakcyjność kuchni regionalnej może być czynnikiem decydującym o wyborze miejsca wypoczynku lub podróży w stopniu wysokim, potwierdziła się. Hipoteza nr 8 zakładająca, że metody promocji produktów regionalnych są nie wystarczające, potwierdziła się. Wnioski W wyniku analizy przeprowadzonych badań zostały sformułowane następujące wnioski: Atrakcyjność potraw sporządzanych wg tradycyjnych receptur, z wykorzystaniem naturalnych składników pozytywnie wpływa na wybór miejsca wypoczynku bądź podróży. Regionalna tradycyjna kuchnia stanowi element wysoce atrakcyjny a jako taki może wpływać na rozwój turystyki kulturowej, a także turystyki w ogóle w badanym rejonie. Ważną rolę w zakresie upowszechnienia produktów tradycyjnych i kuchni regionalnej mają restauracje, karczmy lub oberże, które kultywują tradycję lokalną poprzez wystrój wnętrz i kuchnię regionalną. Kuchnia regionalna może być znakomitym uzupełnieniem innych produktów turystycznych, w szczególności związanych z dziedzictwem narodowym i kulturową turystyką lokalną. Summary Introduction This study concerns the impact of values of the local traditional cuisine on the development of tourism. In this perspective, the region has been designated a cultural Krajny called. land border. It is taken to discuss this issue because of the need and obligation at the same time learn from the cultural heritage for the benefit of the development of society. An example of this giving impetus to the development of tourism may be the use of flavors and aromas of the old Polish cuisine as a tourist attracting tourists. Aim The aim of the research is to determine the impact of cultural and ethnic values of the region (regional cuisine) to develop a tourism function in the region for example Krajna. The area was chosen because of the interest in the subject of promoting elements of folk culture and the feasibility of the topic including their competence, time and technical means. Not without significance is also co-author of his own experience, which initially was the recipient of media folk art, and also the animator. Problems and hypotheses According to the research problem (Frakfort-Nachmias 2001) is an impressive intellectual stimulus response in the form of research. The research problem can be established as an affirmative sentence or questioning, and the same formulation of the problem is to determine the questions that have either no response, or it is not sufficiently precise. It is formulated using specific terms that reflect the empirical phenomena. The hypothesis of the research is preliminary answer to the stated problem, giving up empirically (to be verified in the course of research). In this paper, the following research problems and hypotheses: The root problem: 1. What is the degree of impact on the traditional increase in interest in the region by both potential tourists and locals? Specific problems: 1. What is the level of interest in regional cuisine among the inhabitants of the provinces mainly Wielkopolska, Pomerania and Kujawy-Pomerania (on grounds of administrative Krajna)? 2. What is the knowledge of traditional Polish dishes and regional authorities? 3. Is the public awareness for the concept tavern-style restaurant offering regional food? 4. Is Krajna as a cultural region is recognizable? 5. Are regional cuisine is attractive? 6. Does the attractiveness of regional cuisine can be a decisive factor in choosing a vacation destination or travel? 7. Do the methods promote regional produce sufficient? Main hypothesis: 1. It is assumed that the degree of impact on the traditional increase in interest in the region by both potential tourists and locals is high. Hypotheses particulars: 1. It is assumed that the level of interest in regional cuisine among the inhabitants of the provinces of Wielkopolska, Pomerania and Kujawy-Pomerania (on grounds of administrative Krajny) is at a medium level. 2. It is assumed that knowledge of traditional Polish dishes and regional is at a medium level. 3. It is assumed that in the public consciousness, moderate operating concept restaurant type inn offering regional food. 4. It is assumed that Krajna as a cultural region is recognizable. 5. It is assumed that the regional cuisine is attractive. 6. It is assumed that the attractiveness of regional cuisine can be a decisive factor the choice of vacation destination or travel to a high degree. 7. It is assumed that the methods of promoting regional products are insufficient. Methods, techniques and tools of measurement The research methods used in this study are: diagnostic survey, and as the main technique adopted surveys, a questionnaire consisting of with 6 questions, most of them closed was completed online by 117 respondents attempt. The research was to measure the level of knowledge about regional dishes and interest Krajná as a cultural region. Due to the high rating the attractiveness of traditional dishes of regional cuisine, it was decided to confirm the point of the survey with the help of techniques to support the research process, which are observation and interview-free terrain. Observations and interview free- terrain, which were to some extent the consumer survey, conducted on a sample of 52 people taken care of is that this attempt was represented by people of all ages living in the countryside and in the city. Research Results and Discussion Characteristics of the study group / trials Surveys were conducted on a sample of 117 people with simple random sampling, in the age group 19-30 years. These people are residents of the provinces of Wielkopolskie, Kujawsko-Pomorskie and Pomorskie. The respondents came from both rural and urban areas. verification of hypotheses Verification carried out based on the combined results of the research showed that confirmed seven of the eight established hypotheses. Hypothesis No. 1 assuming that the degree of impact on the traditional increase in interest in the region by both potential tourists and locals alike is high, fully confirmed the. Hypothesis No. 2 assuming that the level of interest in regional cuisine among the inhabitants of the provinces of Wielkopolskie, Kujawsko-Pomorskie and Pomorskie is at the average level, has not confirmed the Hypothesis 3 assuming that the knowledge of traditional Polish dishes and regional authorities is at the average level, confirmed the. Hypothesis No. 4 assuming that in the public consciousness, moderate operating concept restaurant type inn offers regional food, a confirmed. Hypothesis No. 5 assuming that Krajna as a cultural region is recognized, confirmed the. Hypothesis No. 6 assuming that the regional cuisine is attractive, confirmed the. Respondents assessed the regional cuisine as particularly attractive. Hypothesis No. 7 assuming that the attractiveness of regional cuisine can be a decisive factor in choosing a vacation destination or travel to a high degree, confirmed the. Hypothesis No. 8 assuming that the methods of promoting regional products are not sufficient to confirmed. Conclusion As a result of the analysis of the research were formulated following conclusions: 1. The attractiveness of dishes prepared according to traditional recipes, using natural ingredients positively influence the choice of vacation destination or travel. 2. Regional traditional cuisine is part of a highly attractive and as such can affect the development of cultural tourism, and tourism in general in the studied area. 3. An important role in the dissemination of traditional and regional cuisine are restaurants, inns and taverns that cultivate the local tradition through the décor and regional cuisine. 4. Regional cuisine can be an excellent complement to other tourism products, in particular those related to national heritage and local cultural tourism.